Aggravated chemical production of aerosols by regional transport and basin terrain in a heavy PM2.5 pollution episode over central China. (1st February 2023) - Hu, Weiyang; Zhao, Yu; Zhao, Tianliang; Bai, Yongqing; Zhao, Chun; Kong, Shaofei; Chen, Lei; Du, Qiuyan; Zheng, Huang; Lu, Wen; Liu, Weichen; Sun, Xiaoyun
Abstract: Heavy aerosol pollution has occurred frequently over China during wintertime in recent years. Compared to source regions with relatively developed economy (e.g., eastern China), the pollution receptor regions with special topography, such as the Twain-Hu Basin (THB) over central China, have been less analyzed in terms of the main drivers of pollution episodes. In this study, we used the Weather Research and Forecasting model with Chemistry (WRF-Chem) with improved integrated process rate (IPR) analysis to evaluate the contributions of individual physical and chemical processes to PM2.5 variation for a typical aerosol pollution episode in THB in January 2019, and quantified the effects of regional transport and basin terrain on chemical production of PM2.5 . Regional transport of air pollutants from the north was estimated to increase the PM2.5 concentration in THB by 43.5%, attributed mainly to the elevated advection and chemical processes. Furthermore, regional transport enhanced the chemical production of PM2.5 concentration by 110.2 μg m −3, and the number would decline to 7.1 without the effect of basin terrain. Our findings highlighted the critical roles of regional transport of gases precursors and basin terrain on chemical production of aerosols in THB, and emphasized the importance of regional joint controls of emissions for air quality improvement. Highlights: Advection and chemical process were major contributors to a PM2.5 episode in THB. Regional transport elevated the contribution of chemical reaction to PM2.5 growth. Basin terrain accelerated the secondary PM2.5 formation via pollutant accumulation.